The Study of Taxation on Freon - Rahman, Doni Habibur (Interdisciplinary Social Studies, 2022)
Background: Freon consumption has a devastating impact that causes global warming. According to IPCC data, there was an increase in the earth's surface temperature of about 0.74 °C ± 0.18 °C. While in BMKG data, there has been an increase in temperature in Indonesia with an average of 0.03 ° C every year with the meaning that in the last 30 years there has been an increase of 0.9 ° C. So instruments are needed to control the consumption of freon in the form of excise. Aim: This study aims to find out if freon meets its characteristics to be designated as taxable goods. Method: The data used in this study is the result of interviews with 7 sources from regulators, academics, and practitioners. Findings: The results showed that freon qualified and characteristics as a taxable item although there are things that must be studied further. The study also addressed the possibility that excise subjects would seek to find far smaller freons scoring potential global warming or even attempt to avoid excise duty with illegal freons.